Elemental red phosphorus-based photocatalysts for environmental remediation: A review. (July 2021) - Wu, Chunxiao; Jing, Lin; Deng, Jiguang; Liu, Yuxi; Li, Shuang; Lv, Sijie; Sun, Yajie; Zhang, Qichao; Dai, Hongxing
Abstract: The low-cost and environmentally benign elemental red phosphorus (RP) is a new class of photocatalysts with tunable bandgaps (ca. 1.5–2.4 eV) and has a strong visible-light response. It has been considered as a promising metal-free photocatalyst for solving the energy crisis and environmental problems. Unfortunately, due to the low-charge carrier mobility, and serve charge trapping effects, its photocatalytic activity is still restricted in comparison with the traditional compound photocatalysts. Considerable efforts, such as morphology modification, cocatalysts addition, heterostructure construction, charge trapping mitigation, have been conducted to improve the photocatalytic activity of the RP photocatalysts. In this review, the physical and chemical properties and the synthetic strategies of the RP photocatalysts were summarized along with the application in environmental remediation accompanied by the photocatalytic reaction mechanism. Finally, an overview and outlook on the problems and future avenues in designing and constructing advanced RP photocatalysts were also proposed. Graphical abstract: Image 1 Highlights: Current progress of the RP photocatalysts for environmental remediation is summarized. The physical and chemical properties of RP are listed. The preparation methods of the crystalline RP are summarized. Efforts on improving the photocatalytic activity of RP are summarized. An outlook on how to design the advanced RP photocatalysts is presented.